An overview of sedimentation models for Pari river, Malaysia - Abdul Ghani, Nadiatul; Shahin, Mohamed; Nikraz, Hamid (SPACE UTM, 2009)
Rivers are the most important source of water; however, the flow of water changes the patterns of rivers especially during the periods of heavy rain and flooding. The changes in rivers’ patterns are occurred due to sedimentation, which alters the rivers depths and embankments. There are several models currently available in the literature to identify and predict the sedimentation in rivers. These models require several parameters to be quantified in relation to mobility, transport, sediment, channel shape and flow resistance. The aim of this study is to investigate the feasibility of using some of the most commonly used available models for predicting sediment transport in Pari River, Malaysia. The modelling data are collected from the Department of Irrigation and Drainage (DID), Ministry of Natural Resources & Environment, Malaysia. Comparisons of the results obtained from the selected models are used to identify the potential difference among available models.